Exchange rate uncertainty and import prices in the euro area - Boris Blagov (RWI - Leibniz-Institut für Wirtschaftsforschung, 2018)
This paper analyses the effects of exchange rate uncertainty on the pricing behaviour of import firms in the euro area. Uncertainty is measured via the volatility of the structural shocks to the exchange rate in a non-linear VAR framework and is an important determinant of import prices. An increase in exchange rate uncertainty is associated with a fall in prices on average, which suggests that the exchange rate risk is borne by the importers. The analysis utilizes a dataset on industrial import prices, disaggregated by origin of imports. Controlling for intra- and extra-euro area trade is important. – – In diesem Papier werden die Auswirkungen der Wechselkursunsicherheit auf das Preisverhalten von Importfirmen in der Eurozone analysiert. Die Unsicherheit wird über die Volatilität der Strukturschocks auf den Wechselkurs in einem nichtlinearen VAR-Modell gemessen. Sie ist eine wichtige Determinante der Importpreise. Eine Zunahme der Wechselkursunsicherheit ist mit einem durchschnittlichen Rückgang der Preise verbunden, was darauf hindeutet, dass das Wechselkursrisiko durch die Importeure getragen wird. Die Berücksichtigung der Herkunft des Handels (innerhalb oder außerhalb des Euroraums) ist wichtig für die Ermittlung der Auswirkungen von Wechselkursbewegungen auf die Preisentwicklung.
Keywords: C11; C22; F31; 330; exchange rate uncertainty; exchange rate pass-through; non-linearities; import price inflation; extra-euro area trade